2013
DOI: 10.4021/jocmr1160w
|View full text |Cite
|
Sign up to set email alerts
|

A Single Dose of Amoxicillin and Dexamethasone for Prevention of Postoperative Complications in Third Molar Surgery: A Randomized, Double-Blind, Placebo Controlled Clinical Trial

Abstract: BackgroundThe aim of this study was to assess the efficacy of a single prophylactic dose of amoxicillin and/or dexamethasone in preventing postoperative complications (PC) after a surgical removal of a single mandibular third molar (M3).MethodsThis study is a randomized, placebo controlled clinical trial. Four groups were included: Group 1 (G1) included a prophylactic dose of 2 g of amoxicillin and 8 mg of dexamethasone; Group 2 (G2) included a prophylactic dose of 2 g of amoxicillin and 8 mg of placebo; Group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 29 publications
3
25
0
4
Order By: Relevance
“…This corroborates what has been theoretically established and coincides with the data reported in other studies. [26][27][28] Results showed less trismus in the group treated with post-surgical dexamethasone in the first three postoperative evaluations, outcome that was reverted on the seventh day. However, these differences were not significant, coinciding with the clinical trials conducted by Moore et al, 29 which showed that the group that received preoperative rofecoxib and intraoperative dexamethasone had a mouth opening reduction of only 23.7%, compared to the placebo group, which showed a 43.2% reduction; p>0.05.…”
Section: Discussionmentioning
confidence: 99%
“…This corroborates what has been theoretically established and coincides with the data reported in other studies. [26][27][28] Results showed less trismus in the group treated with post-surgical dexamethasone in the first three postoperative evaluations, outcome that was reverted on the seventh day. However, these differences were not significant, coinciding with the clinical trials conducted by Moore et al, 29 which showed that the group that received preoperative rofecoxib and intraoperative dexamethasone had a mouth opening reduction of only 23.7%, compared to the placebo group, which showed a 43.2% reduction; p>0.05.…”
Section: Discussionmentioning
confidence: 99%
“…11 Similar protocols were used in several studies with varying results on the efficacy of the prophylactic treatment. 8,27 Ren et al 28 performed a meta-analysis of 23 studies on the effectiveness of antibiotic prophylaxis in third molar surgery and concluded that when systemic antibiotics are administered before surgery, they are effective in reducing the frequency of wound infections. In contrast, in a review of published clinical trials on the efficacy of antibiotic prophylaxis, Oomens et al 29 reported a lack of evidence to support the use of prophylactic antibiotics in lower third molar surgery.…”
Section: Discussionmentioning
confidence: 99%
“…(48) Apesar da administração da amoxicilina no intuito de reduzir complicações pós-operatórias ser objeto de controvérsias, os estudos vigentes revelam que essa prática não apresenta eficácia clínica comprovada e, portanto sua descontinuação deveria ser considerada. (17,45,49,(58)(59)(60)(61)(62)(63) Assim, a melhor forma de prevenir complicações inflamatórias e pós --operatórias permanece sendo o controle vigoroso da cadeia asséptica e a utilização de técnicas cirúrgicas apropriadas. (17,64,65)…”
Section: Discussionunclassified